Ferritina liquórica no diagnóstico etiológico de meningites em pediatria - Barcelos, Andrea Lucia Machado (2016)
Objective: To compare the ferritin levels in the cerebrospinal fluid (CSF) of children with clinical suspicion bacterial meningitis, viral and non-meningitis cases. Methods: A cohort, historical and contemporary study was conducted in two tertiaries hospitals in the southern Brazil. All children included were between 28 days and 12 years old with suspected acute meningitis. Ferritin levels in the CSF were measured in the period between 2005 and 2015 and they were compared among patients with bacterial meningitis, viral meningitis and non-meningitis. Results: Eighty one patients were included. The median age was 24 (IQR8.0-69.0) months. It was identified 32 patients with viral meningitis (39%), 23 with bacterial (28%) and 26 as non-meningitis (32%). Demographic and clinical characteristics at admission were similar between groups. The median CSF ferritin was 52.8 (IQR30.7-103.0) for the bacterial meningitis group, 4.1 (IQR3.0-6.7) for the viral group and 4.0 (IQR2.0-2.3) for the non-meningitis group (p<0.001). When compared in pairs, bacterial meningitis was distinguished from viral meningitis (p <0.001) and non-meningitis (p <0.001). However, ferritin levels failed to distinguish viral meningitis from non-meningitis. The CSF ferritin, with a cut-off value of 16 ng/ml, had 100% sensitivity and 98.3% specificity for bacterial meningitis. Conclusion: CSF ferritin was shown to be an excellent marker for identifying and discriminating bacterial meningitis in children with clinical symptoms of this disease.